Effectiveness Of Broilers (Gallus sp.) Hypophyes Extract On Reproductive Performance And Survival Of Sangkuriang Catfish (Clarias sp.) Larvae - Lesik, Adevalentin; setyawati, Iriani; Manik Ermayanti, NI Gusti Ayu (Metamorfosa: Journal of Biological Sciences, 2021)
The pituitary gland of broiler chickens ( Gallus sp .) is empirically known to have gonadotropins to accelerate ovulation in fish. This research was conducted to determine the reproductive performance and survival of sangkuriang catfish ( Clarias sp .) Larvae of adult male and female mature gonads by 20 pairs. This study used a Completely Randomized Design consisting of 4 treatments and 5 replications to obtain 20 experimental units. Doses of pituitary extract used is without injection of pituitary chicken pituitary extract (P0), injection of pituitary chicken pituitary extract with a dose of 600 mg/kgbb (P1), 900 mg/kgbb (P2) and 1200 mg/kgbb sangkuriang catfish (P3). Intramuscular injection of extracts in the ventral dorsal fin with a volume of 0.5 mL/kgbb. Descriptive data analysis for gonad maturity level, ovulation response, egg performance. Statistical analysis of data for morphometric aspects using the Wilcoxon test, for latency time, relative fecundity, fertilization success, hatching success, and larval survival aspects using One Way Anova using SPSS version 25. The results of statistical analysis showed significant differences in reproductive performance (relative latency and fecundity time), successful fertilization and successful hatching of eggs, but there was no significant difference in survival (number of live larvae, length and weight) larvae of sangkuriang catfish ( Clarias sp .). Broiler chicken pituitary extract ( Gallus sp .) can improve reproductive performance, fertilization and hatching success but does not affect egg performance and survival of sangkuriang catfish ( Clarias sp .) larvae.     Keyword : catfish, pituitary extract, reproduction, survival